SUSTAINABILITY REPORTS AS DRIVERS OF SOCIAL RESPONSIBILITY IN HEALTHCARE COMPANIES (2023)
Sustainability reports are public disclosures of the economic, environmental, and social impacts of organizations in achieving the Sustainable Development Goals (SDGs) and their social responsibility actions. This knowledge is important to identify the actions that the healthcare sector is undertaking to fulfill these objectives and to design strategies that foster social responsibility processes aimed at strengthening organizations and advancing theircommitments in this area. The objective is to identify the perception of healthcare companies have regarding the importance, relevance, impact, and implementation of strategies to contribute to the achievement of the SDGs. The study has a descriptive scope, a quantitative approach, and a cross-sectional design. The research addresses the concept of sustainability from the perspective of business people through the application of a structured instrument with four variables: Perception of the relevance and feasibility of implementing sustainability reports, Perception of the impact generated by the company, Perception and management of environmental impact, and Perception and influence of indicators. To collect information from the primary source, a semi-structured interview with 21 questions was used, which was validated with a Cronbach's Alpha of 0.758. The sample was defined with a confidence level of 95% for a total of 281 companies. The results show that 45% of business people consider that their activities have a positive impact on the dimensions of sustainable development, 64% are concerned about their contribution to the achievement of the SDGs, and 30% believe that these contributions should be mandatory and disclosed to society, therefore, it is recommended to move towards the consolidation of sustainability reports as determiners of social responsibility.